Motivation of Volunteers in Providing Assistance to Disaster Victims - Mulyaningsih Mulyaningsih; Hermawati Hermawati (Indonesian Journal of Global Health Research, 2023)
Indonesia is a disaster-prone area. Disasters that occur can have various impacts and require help. Assistance can be done by health workers and the general public, especially volunteers. The factors that underlie or motivate a person to become a volunteer are manifold. To support volunteer activities, it is necessary to provide sufficient knowledge and skills. This study aims to obtain an overview of the motivation of volunteers in providing assistance to disaster victims. This research uses qualitative methods with a phenomenological approach. The number of participants in this study was four volunteers. The data collection technique carried out in this study was by conducting indeph interviews to all participants. The results of the interview were then analyzed thematically. Based on the analysis, 5 themes were obtained, namely the motivation to become a volunteer, the feeling of volunteers in providing assistance to disaster victims, the obstacles found in providing assistance, the support obtained as volunteers, and the expectations of volunteers in carrying out their duties.